Base‐Mediated Transition‐Metal‐Free Dehydrative C−C and C−N Bond‐Forming Reactions from Alcohols. Issue 12 (25th April 2019) - Porcheddu, Andrea; Chelucci, Giorgio
Abstract: In recent years, there has been an increasing interest in using alcohols as alkylating agents for C−C and C−N bond‐forming processes employing mainly TM‐catalysts. Although BH‐catalysis looks like a green atom economy process since water is the only by‐product, it often suffers from one or more drawbacks, such as the use of expensive noble metal complexes, capricious ligands, and toxic organic solvents. Therefore, straightforward, efficient, atom economy and environmentally benign alternative protocols are desirable. This review aims to summarize the current knowledge within the published literature about dehydrative processes developed without TM‐catalysts. The most recent contributions to this topic have been reviewed keeping into account the new findings reported in this area. The features, strengths, and limitations of these alcohol‐based C−C and C−N bond‐forming processes has also been taken into account. Abstract : Dehydrative formation of C−C and C−N bonds with alcohols